Materiais multifuncionais inorgânicos para geração de precursores de espécies reativas de oxigênio e entrega controlada de fármacos: Uma abordagem teórico-computacional - Santos, Jeziel Rodrigues dos (Universidade Federal de São Carlos, 2025)
This thesis investigates, through theoretical-computational methods, the development and characterization of two multifunctional materials intended for catalytic and therapeutic applications. In the first part, silver alpha tungstate was evaluated as a functional material for the generation of reactive oxygen species. The optimization calculations of the lattice parameters and the construction of morphologies via the Wulff method evidenced the predominance of the (101) surface in the formation of a hexagonal bar, which, combined with the specific distribution of oxygen vacancies and the configuration of silver quantum clusters, showed a high capacity for the selective adsorption of H₂O and O₂ molecules. These interactions promote the formation of reactive precursors, essential for oxidation processes and photocatalytic applications, confirming the relevance of silver alpha tungstate as a catalyst in environmental processes and in the degradation of pollutants. In the second part, the thesis addresses the application of boron nitride nanotubes as a nanocarrier for the drug FLU, an antiandrogen used in the treatment of prostate cancer. Through DFT calculations, it was observed that the encapsulation of FLU in BNNT does not promote significant structural changes, maintaining the stability of the system both in vacuum and in aqueous media. The results reveal favorable interactions, characterized by negative adsorption energies, which indicate a charge transfer from BNNT to FLU, facilitating the formation of a stable complex. Molecular dynamics simulations corroborated the maintenance of the encapsulated drug over 50 ns, with analyses of center of mass distance, RMSD and radial distribution functions confirming the structural integrity of the system. In addition, the analysis of the binding free energy by MM and PBSA showed that van der Waals and electrostatic interactions are determinants for the stability of the FLU complex with BNNT. Together, the results demonstrate the potential of the studied materials both in promoting catalytic reactions and in improving drug delivery, opening new perspectives for the development of innovative multifunctional systems in environmental and therapeutic catalysis.
Inorganic materials multifunctional materials for generation of reactive oxygen species precursors and controlled drug release: A theoretical-computational approach
Keywords: Semicondutores; Alpha tungstato de prata; Oxidação de proteínas; Nanocarreadores; Transporte de fármacos; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA::QUIMICA TEORICA; ENGENHARIAS::ENGENHARIA ELETRICA::MATERIAIS ELETRICOS::MATERIAIS E COMPONENTES SEMICONDUTORES; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::FISICO QUIMICA INORGANICA